Pengaruh Lama Perendaman Fiber Reinforced Composite dengan Fiber Sisal (Agave sisalana) Terkalissai dalam Saliva Buatan Terhadap Perubahan Dimensi - Wibowo, Diva Agrita Dentisia; Widjijono, Widjijono; Siswomihardjo, Widowati (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2018)
Fiber reinforced composite is a material composed of matrix and reinforced by fiber. Fiber sisal is a natural fiber an alternatives synthetic fiber developed as dental material. Resin composite matrix is a hydrophilic substance that cause dimensional change. Alkalization of sisal fiber reduces the ability of hydrophilic sites which affects the dimensional changes. The aim of this study was to determine how different period of immersion affect dimensional change in samples. The samples used in this research were FRC made from flowable resin composite (Master Flow, Brazil), and alkalized sisal fiber. The samples were shaped into cuboid measuring 25x2x2 mm. Fiber was placed in the middle of sample with continuous unidirectional direction and then irradiated for 20 seconds using LCU. A total of 16 samples were divided to 4 groups, each group with the different period of immersion 0, 7, 14 and 21 days respectively. Dimensional changes were measured by the final dimension minus the initial dimension. Dimensional change was measured by the length, width, and height using digital sliding caliper with 0.001 mm nonius. The samples were immersed in the artificial saliva with pH 7. The data was analyzed using one way Anova and followed by LSD0.05. The result shows the mean value and standard deviation of dimensional changes with period of immersion at 0, 7, 14 and 21 days were 0.264±0.085, 2.856±0.089, 4.417±0.115 and 4.294±0.087 mm3. The F value obtained from one way Anova was 1.640±103 and the significance was 0.001 (p<0.05), indicated a significance difference. LSD presented a significance difference of mean to all treat,ent except for 14th and 21th day. This study concluded that various period of immersion increase effect to the dimensional changes of FRC with alkalized fiber sisal.